(untitled) (Medico Legal Update, 2020)
The abnormal tissues which are originated from the brain cells are known as brain tumor. It may be cancerous tumor or non-cancerous tumor; these can cause pressure inside the skull to increase the tumors. This damages the brain and become life-threatening. The main cause of brain tumor is still unknown. The early diagnosis is required otherwise it increases the mortality rate. The segmentation of tumor part is essential to identify the affected area in the brain. In this study, an effective method for Brain Tumor Segmentation (BTS) is presented. The BTS system uses Discrete Wavelet Transform (DWT), K-Means Clustering (KMC) algorithm and morphological operations for segmentation. Firstly, the input brain images are given to DWT for decomposition and it produces lower and higher frequency sub-band coefficients. Then the Inverse DWT (IDWT) is applied to reconstruct the image. The reconstructed image is given to KMC technique for segmentation. Then the unwanted regions are removed by morphological operations to detect the brain tumor in the given input image.